(untitled) (Journal of Entrepreneurship and Business, 2021)
The study aims to determine the factors influencing customer satisfaction in online shopping among Malaysian youth. Online shopping is increasingly popular among Malaysians, including teenagers, due to its time-saving, convenience and availability anywhere and anytime. As online technology is still new in Malaysia, online sellers find it challenging to retain online buyers. The study adopted a survey through a quantitative approach by distributing questionnaires among the youth in Malaysia. The findings indicated that product quality, security, and shipping significantly affect customer satisfaction in online shopping. Furthermore, the study provides recommendations for online sellers and policymakers in enhancing the strength of online platform as the best transaction for customers